Analisis Definisi Sahabat Dalam Beberapa Karya Syiah Melayu: An Analysis of the Definition of Companion in Several Malay Shiite Works - Mas’od, Mohd Aizam; Hamat, Mohd Fauzi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2018)
The belief of Shiite has been spread in Malaysia by the 1980s after the Iranian revolution in 1979. In the Malaysian context, dissemination of Shiite to the Malay community occurred through a variety of ways. Among the spreading mediums that had a tangible impact were the spread of Malay Shiite works. Various issues arose in the works such as the issues of Imamah, Imam al-Mahdi, mut‘ah marriage and the justice of the companions. However, this article will focus on the definition of the companions in the works. Using a qualitative approach, this study is based on two methods of assessment, namely data collection and data analysis. Through the method of documentation in the method of data collection, this study refers to two selected Shiite Malay works entitled Meniti Titian Kebenaran by Khair Izzah and Perempuan Nan Bercinta by Faisal Tehrani. Whereas comparative method is used in analyzing data by comparing the definition of companions according to Shiite and Ahl al-Sunnah wa al-Jama‘ah (Sunnite). The study concludes that the concept of companions from the perspective of Malay Shiite works is equivalent to the original doctrine of Shi‘ah Imamiyyah Ithna ‘Ashariyyah. It begins with the understanding of the term of companion that was maintained according to the meaning of the language. The term companion does not bring any significant meaning from the point of shara` except merely symbolising someone who socialised with Prophet PBUH during his lifetime. This belief is contrary to Ahl al-Sunnah wa al-Jamа‘ah. This is because the term companion has a strong foundation based on texts of Shari‘ah. Understanding the term of companion with the meaning of the language solely regardless of the proponents submitted by the Shari‘ah with the correct understanding can cause the failure to understand the concept of companion as a whole.